Understanding the deformability of 2D van der Waals materials from the perspective of chemical bonds - Haoran Huang; Zhiqiang Gao; Ling Fu; Kunpeng Zhao; Jiawei Zhang; Tian-Ran Wei; Xun Shi (npj Computational Materials)
Abstract Exceptional room-temperature plastic deformability has been recently uncovered in a series of two-dimensional (2D) van der Waals (vdW) crystals, adding a new facet to these materials alongside the rich physical properties. Although several mechanisms have been proposed to interpret the deformation of specific materials, a deep and systematic understanding is still missing to rationalize and compare the deformability for a variety of vdW materials. In this work, focusing on typical hexagonal vdW crystals such as graphite, h-BN, transition metal dichalcogenides (TMDCs), and IIIA-VIA compounds, the deformation parameters (slip barrier energy, cleavage energy, elastic modulus) and bond features are calculated, and their correlations are systematically studied. Noticeably, there is a strong positive relation between cross-layer slip/cleavage energy, in-plane modulus, and the intralayer bond strength. The IIIA-VIA compounds (GaS, GaSe, InSe) are predicted to show a larger deformability factor, probably due to their weaker and softer chemical bonds. Moreover, it is anticipated that the deformability can be further modulated by constructing superlattice structures. These findings will facilitate the understanding and development of a variety of deformable 2D inorganic semiconductors as both few-layers and bulks.